Massive Africanized honeybee stings in two hair sheep and a mare. (15th April 2020) - Veado, Henrique C.; Conceição, Raffaela S.; Nogueira, Kaique; Fino, Tayná Cardim M.; Silva, Anahi S.; Castro, Marcio B.; Soto-Blanco, Benito; Câmara, Antonio Carlos Lopes
Abstract: The findings of massive Africanized honeybee stings in two hair sheep and a mare are reported. One sheep died 15 h after attack, and the survivors developed skin necrosis on the sting sites. Pathological evaluation revealed necrosis in the dermis, degeneration of the tubular epithelial cells, and multifocal hemorrhages in heart and spleen. The massive attack by Africanized honeybees induced lesions in the skin, heart, muscles, kidneys, and lungs. Highlights: Only sporadic reports of honeybee stings in cattle and horses have been published. There is no report in sheep. Epidemiology, clinical, and laboratory features of Africanized honeybee attacks in two hair sheep and a mare are reported. Pathological findings of a fatal case in a sheep and development of the skin-biopsy lesions in another sheep are presented. Lesions in the skin, heart, muscles, kidneys, and lungs induced by massive Africanized honeybee stings are presented.